Applying E-Module Based on Problem Based Learning to Increase Scientific Literacy and Decrease Student’s Misconception in Ecology at Grade X MIA 6 of SMA N 1 Karanganom Academic Year 2014/2015 - Citra Devi Imaningtyas; Puguh Karyanto; Nurmiyati Nurmiyati; Lilik Asriani (Universitas Sebelas Maret, 2015)
This research aims to increase scientific literacy and decrease student’s misconception at grade X MIA 6 of SMAN 1 Karanganom by applying e-module based on the concept of Problem-Based Learning (PBL). The type of the research was a classroom action research which consisted of two cycles. Each cycles applied: planning the learning activity, implementing the plan, observing the students’ activity and finally complimenting the whole activities in one cycle. The research subject was graders X MIA 6 of SMAN 1 Karanganom, which were 11 boys and 23 girls. The data validation used triangulation method. The data of the research were obtained by formulating the test, observation and interview. The obtained data were analyzed using the descriptive technique. The results of the research showed the implementation of e-module based on the concept of Problem-Based Learning (PBL) decrease the students’ misconception on the ecology subject with the explanation: the population concept decreased 21%, the comunity concept run into reduction 22%, the ecosystem concept went down 21% and the ecology concept in ‘Science, environment, technology, and society’ context reduced 26%. The analysed result also indicated that the scientific literacy has increased 20.6%. The result of the research evidenced the implementation of e-module based on the concept of Problem-Based Learning could increase the scientific literation and decrease the students’ misconception on the ecology subject.Keywords: E-module with based Problem-Based Learning, misconception, scientific literacy